2007
DOI: 10.1152/ajpendo.00599.2006
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid repletion does not decrease muscle protein catabolism during hemodialysis

Abstract: Intradialytic protein catabolism is attributed to loss of amino acids in the dialysate. We investigated the effect of amino acid infusion during hemodialysis (HD) on muscle protein turnover and amino acid transport kinetics by using stable isotopes of phenylalanine, leucine, and lysine in eight patients with end-stage renal disease (ESRD). Subjects were studied at baseline (pre-HD), 2 h of HD without amino acid infusion (HD-O), and 2 h of HD with amino acid infusion (HD+AA). Amino acid depletion during HD-O au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 52 publications
0
22
0
1
Order By: Relevance
“…They are not built into the muscles, as we would expect during muscle reconstruction after proteolysis. Amino acids are transported to the liver where they are utilized probably to the synthesis of acute phase proteins [7, 60]. Experimental attempts to block TNF α and NF κ B inhibited skeletal muscle proteolysis [61, 62].…”
Section: The Mechanisms Of the Sarcopenia Development In Elderly Pmentioning
confidence: 99%
“…They are not built into the muscles, as we would expect during muscle reconstruction after proteolysis. Amino acids are transported to the liver where they are utilized probably to the synthesis of acute phase proteins [7, 60]. Experimental attempts to block TNF α and NF κ B inhibited skeletal muscle proteolysis [61, 62].…”
Section: The Mechanisms Of the Sarcopenia Development In Elderly Pmentioning
confidence: 99%
“…There is a gradual increase in muscle wasting as kidney function deteriorates towards the need for RRT [22], and defective protein metabolism is observed in those treated with regular dialysis [23] suggesting that both renal failure itself and the dialysis process contribute to this catabolic state [24,25]. Specifically HD has been shown to promote muscle and whole body protein degradation [24,26].…”
Section: Factors Leading To Poor Physical Function In Ckdmentioning
confidence: 99%
“…There is a gradual increase in muscle wasting as kidney function deteriorates towards the need for RRT [22], and defective protein metabolism is observed in those treated with regular dialysis [23] suggesting that both renal failure itself and the dialysis process contribute to this catabolic state [24,25]. Specifically HD has been shown to promote muscle and whole body protein degradation [24,26]. Chronic metabolic acidosis (which occurs in nearly all patients with advanced CKD) contributes to this increased protein degradation [23] by activation of the ubiquitin-proteasome pathway [27], possibly initiated by impairing the transport and utilization of amino acids [28].…”
Section: Factors Leading To Poor Physical Function In Ckdmentioning
confidence: 99%
“…Consequently, clinical studies in CKD patients have shown links between inflammatory cytokines and muscle wasting [3,75e77]. A main mechanism of inflammationinduced wasting is via activation of NF-kB and ATPubiquitin-dependent proteolytic pathways (leading to cleavage of a characteristic 14 kDa actin fragment) that cause muscle wasting [78]. As Raj et al [79] observed ineffective utilization of exogenous amino acids for muscle protein synthesis during HD, they hypothesized that increased skeletal muscle expression of IL-6 further augmented muscle protein catabolism in ESRD.…”
Section: Direct Catabolic Effects Of Inflammationmentioning
confidence: 99%